2022
DOI: 10.3390/pharmaceutics14112488
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to Pharmaceutical 3D-Printing Omitting the Need for Filament—Investigation of Materials, Process, and Product Characteristics

Abstract: The utilized 3D printhead employs an innovative hot-melt extrusion (HME) design approach being fed by drug-loaded polymer granules and making filament strands obsolete. Oscillatory rheology is a key tool for understanding the behavior of a polymer melt in extrusion processes. In this study, small amplitude shear oscillatory (SAOS) rheology was applied to investigate formulations of model antihypertensive drug Metoprolol Succinate (MSN) in two carrier polymers for pharmaceutical three-dimensional printing (3DP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Small batch sizes as well as small sampling sizes increase the errors found. Deviation regarding the drug content has been shown in previous studies as well [ 20 , 34 , 35 , 36 ], which might be reduced by in-line quality control mechanisms.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Small batch sizes as well as small sampling sizes increase the errors found. Deviation regarding the drug content has been shown in previous studies as well [ 20 , 34 , 35 , 36 ], which might be reduced by in-line quality control mechanisms.…”
Section: Resultsmentioning
confidence: 86%
“…It was shown that vacuum compression modeling (VCM) is a useful tool for the simulation of extruded samples in order to correctly predict extrusion parameters. Also, temperature as a crucial parameter for printability was predicted by melt rheology experiments [ 20 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seoane-Viaño et al [ 29 ] also had to perform a prior step, in particular a dry granulation step, to obtain a material with sufficient flowability for the successful direct extrusion and printing of tablets using this 3D printer. This was also the case of Pflieger et al [ 30 ], who used granules previously prepared by HME as feeding material in the single-screw extrusion-based printer Flexdose TM (Digital Health Systems GmbH (Schwäbisch Gmünd, Germany)) to produce immediate-release tablets.…”
Section: Resultsmentioning
confidence: 99%
“…Pflieger et al [ 30 ] investigated the relationship between the viscosity of a material and its printability. For this purpose, they printed cylindrical tablets containing 25% w / w of metoprolol succinate and either Kollidon ® VA64 (KVA64) plasticized with polyethylenglycol (PEG) 6000 or Eudragit ® EPO and performed rheological measurements of the extruded blends using Small Amplitude Oscillatory Shear tests (SAOS).…”
Section: Resultsmentioning
confidence: 99%